2019
DOI: 10.12965/jer.1938622.311
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Pilates participants’ empirical values on their emotional responses and behavioral intentions

Abstract: This study aimed to investigate the relationship between the empirical value of Pilates participants and their emotional response and behavioral intention. For this study, 286 participants who participated in Pilates classes in Seoul and Gyeonggi-do in 2019 were selected using the convenience sampling method. For data processing, frequency, exploratory factor, reliability, correlation, and multiple regression analyses were performed using PASW ver. 23.0. The empirical values of the Pilates participants had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
1
0
7
Order By: Relevance
“…The results of the systematic search are shown in a Prisma flow diagram (Moher, Liberati; Tetzlaff, & Altman, 2009); in Figure 1, 338 studies were retrieved, 278 duplicates removed and 30 studies were identified form 60 titles. We excluded 22 studies after screening by abstract due to the following reasons: out of study scope (e.g., they were not focusing exclusively on the Pilates approach or the participants views; n = 5; Amaral et al, 2019; Brewin & Nannini, 2014; Carling, Nilsagård, & Forsberg, 2018; Kirby, Broom, Adams, Sibbritt, & Refshauge, 2014; Martin, 2017); quantitative data selection ( n = 9; Baillie, Bacon, Hewitt, & Moran, 2019; Franco, Franco, Oliveira, Padula, & Cabral, 2018; Hassani et al, 2018; Kovách, Plachy, József, & Barthalos, 2013; Martínez‐Sánchez, Martínez‐García, Bueno‐Antequera, & Munguía‐Izquierdo, 2020; Roh, 2016a; Stan et al, 2012; Vieira, Faria, Wittmann, Teixeira, & Nogueira, 2013; von Sperling de Souza & Brum Viera, 2006); included only healthy participants ( n = 5; Ahearn, Greene, & Lasner, 2018; Caldwell, Adams, Quin, Harrison, & Greeson, 2013; Mazzarino, Kerr, & Morris, 2018; Roh, 2018, 2019a); included only Pilates instructors without a physiotherapy educational background ( n = 3; Lewitt, McPherson, & Stevenson, 2019; Roh, 2016b, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the systematic search are shown in a Prisma flow diagram (Moher, Liberati; Tetzlaff, & Altman, 2009); in Figure 1, 338 studies were retrieved, 278 duplicates removed and 30 studies were identified form 60 titles. We excluded 22 studies after screening by abstract due to the following reasons: out of study scope (e.g., they were not focusing exclusively on the Pilates approach or the participants views; n = 5; Amaral et al, 2019; Brewin & Nannini, 2014; Carling, Nilsagård, & Forsberg, 2018; Kirby, Broom, Adams, Sibbritt, & Refshauge, 2014; Martin, 2017); quantitative data selection ( n = 9; Baillie, Bacon, Hewitt, & Moran, 2019; Franco, Franco, Oliveira, Padula, & Cabral, 2018; Hassani et al, 2018; Kovách, Plachy, József, & Barthalos, 2013; Martínez‐Sánchez, Martínez‐García, Bueno‐Antequera, & Munguía‐Izquierdo, 2020; Roh, 2016a; Stan et al, 2012; Vieira, Faria, Wittmann, Teixeira, & Nogueira, 2013; von Sperling de Souza & Brum Viera, 2006); included only healthy participants ( n = 5; Ahearn, Greene, & Lasner, 2018; Caldwell, Adams, Quin, Harrison, & Greeson, 2013; Mazzarino, Kerr, & Morris, 2018; Roh, 2018, 2019a); included only Pilates instructors without a physiotherapy educational background ( n = 3; Lewitt, McPherson, & Stevenson, 2019; Roh, 2016b, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…Las mejoras emocionales inherentes a los ejercicios de Pilates y yoga son fundamentales para aumentar la capacidad de recuperación del ego y aliviar los síntomas de depresión. Estos hallazgos son similares a los obtenidos en otros recientes estudios previos sobre la incidencia de la actividad física en el control de las emociones y su impacto en la salud mental de sus participantes (Edwards et al, 2017;Mejía et al, 2021;Roh, 2016;Roh, 2019;Zach et al, 2021). Los resultados de nuestra revisión confirman correlaciones altas entre la función emocional y social con la salud mental, poniendo en relevancia la importancia de los aspectos emocionales y sociales, como factores fundamentales en la salud mental.…”
Section: Fuentes De Mejora Y Efectos Beneficiosos De Pilates Y Yoga E...unclassified
“…Joseph H. Pilates (1880-1967) criou um método de atividade física com o objetivo de desenvolver de forma equilibrada a mente e o corpo [40][41][42][43] . O método Pilates é baseado nas filosofias e técnicas orientais como a yoga, as artes marciais, meditação zen, balé, e exercícios gregos e romanos antigos 41 .…”
Section: Método Pilatesunclassified